An Internet‐based programme to promote adequate UV exposure behaviour in adolescents in Spain. (14th February 2012) - Buendía Eisman, A.; Arias Santiago, S.; Moreno‐Gimenez, J.C.; Cabrera‐León, A.; Prieto, L.; Castillejo, I.; Conejo‐Mir, J.
Abstract Background The exponential rise in the incidence of cutaneous cancers underscores the need to promote primary prevention. Adolescents are highly familiar with the use of Internet, and new technologies and Internet systems have proven especially useful to educate this age group in other health problems. To date, there have been no reports of Internet‐based primary prevention campaigns for adolescents against skin cancer. Objectives To determine the knowledge and behaviour of a Spanish adolescent population in relation to sun exposure through an Internet‐based system and to describe the use of an Internet‐based school intervention programme to improve the sun exposure knowledge and behaviour in adolescents. Methods The cross‐sectional study included 2170 school pupils aged between 12 and 16 years from public secondary schools. Pupils in the participating centres completed the survey via the website, which contained a total of 35 questions and three information blocks. For the intervention programme, a sub‐sample of 12 secondary schools (total of 1290 pupils) was randomly selected. Results About 56.7% of the female pupils and 52.6% of the male pupils reported having suffered from sunburn in the previous summer. Sunburn risk increased with the frequency of sun exposure between 12 and 6 pm (OR of 3.59), null knowledge of the negative effects of sun exposure (OR of 2.102), the use of sun protection cream (OR of 0.695 for non‐use) and physical sun protection measures (OR of 2.21 for 0–1 physical measures). A significant reduction in self‐reported sunburns was observed in the quasi‐experimental group in comparison with controls after adjusting for sex and inland or coastal location of the centre (OR = 0.45, 95% CI = 0.23–0.87, P = 0.018). Adjusted OR showed that there was a significant improvement in the use of physical measures, use of sun cream, frequency of sun cream application every 2 h and use of protection on cloudy days. Conclusions This is the first study to demonstrate that a programme entirely conducted via Internet significantly reduces by half self‐reported sunburn risk in an adolescent population achieving very high satisfaction rates.